2002
DOI: 10.1116/1.1487872
|View full text |Cite
|
Sign up to set email alerts
|

Phase behavior in the CdTe–CdS pseudobinary system

Abstract: Polycrystalline thin films deposited by coevaporation of CdTe and CdS form metastable single-phase CdTe–CdS alloys. Subsequent heating in a kinetic-enhancing ambient segregates CdTe1−xSx and CdS1−yTey phases from the original alloy phase. The equilibrium miscibility gap between the resulting CdTe1−xSx and CdS1−yTey alloy phases is determined for CdTe1−xSx films with initial x ∼ 0.4 treated from 360 to 700 °C. At 625 °C, the equilibrium compositions correspond to published results for mixed crystals. Below 625 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 11 publications
5
12
1
Order By: Relevance
“…This is consistent with Dhere's result [8]. McCandless's results also suggest that at 625-°C growth temperature, CdCl 2 and O 2 only play a pure kinetic role [14].…”
Section: A Nanorange S-te Interdiffusion Within Grainssupporting
confidence: 83%
See 1 more Smart Citation
“…This is consistent with Dhere's result [8]. McCandless's results also suggest that at 625-°C growth temperature, CdCl 2 and O 2 only play a pure kinetic role [14].…”
Section: A Nanorange S-te Interdiffusion Within Grainssupporting
confidence: 83%
“…This layer locates mostly inside CdTe near the interface, which is probably due to the different diffusion coefficients of S and Te. The thermochemical and kinetic study by McCandless et al [14], [15] shows that S diffuses in CdTe more easily than Te diffusion in CdS below 625°C. Note that this nanoscale interdiffusion is not caused by the beam broadening effect, as the EELS simulation in supplemental Figure S5 of our previous publication [16] has revealed that the beam spreading size is ß0.5 nm with the same sample and microscopy condition.…”
Section: A Nanorange S-te Interdiffusion Within Grainsmentioning
confidence: 98%
“…Single-phase films, however, have been grown within the miscibility gap, implying non-equilibrium growth methods were used. The phases generally separated after a CdCl2 HT [6][7][8]. We found similar behavior in this study.…”
Section: Introductionsupporting
confidence: 87%
“…The best simulation indicates that x = 0.15 and y = 0.1. This result is close to but different from the value reported by McCandless et al (2002) and Dhere et al (2002). It can be explained that the solubility limits of solid solution CdTe 1Àx S x and CdS 1Ày Te y were varied with the growth technique and the annealing conditions (McCandless et al, 2002;Dhere et al, 2002;Santana-Aranda and Meléndez-Lira, 2001).The amount of tellurium diffusion is found to be less than sulfur diffusion due to the lager atomic radius of tellurium compared to sulfur.…”
Section: Resultscontrasting
confidence: 58%